SPECIMEN OF TACHYSURUS PLATYSOMUS WITHOUT PELVIC FINS - Menon, N Gopinatha (Indian Journal of Fisheries, 2011)
A single specimen of Tachysurus platysomus, from the trawl net catchesfrom the Gulf of Mannar, without pelvic fins is described with reference tosimilar findings dsewfaere. There are many instances of the total absence cAthe paired and uopaiied fiiÂ» among fishes (Dawson, 1964). But there are onlyfew records of almormalities among siluroid fishes.